Potency of Bancassurance-A General Overview - Diksha Sadana; Dr. Kamalpreet Kaur (Journal of Corporate Finance Management and Banking System, 2024)
From a constrained, closed economy in the 1950s to an open, liberalized economy as it is today, India's economy has come a long way. It took over 40 years to bring about the required reforms for the bilateral growth of the Indian economy relative to the global economy; hence the transformation did not occur in a single day. The nationalization of banks provided the sector with much-needed capital where the flow of funds was constrained, and the sector had a substantial impact on the development of the economy. Private players' arrival has significantly altered the way business is conducted, and they have chosen to create a new distribution model called "Bancassurance" that will allow them to reach a larger audience through the banking system, or bank branches. Overall, we can conclude that bancassurance is a ‘distribution model’ that has been established in a way that ensures all stakeholders will anticipate receiving a positive return on their investment. But this model's efficacy usually remains a matter of debate. Since the year 2000, practically all of the literature has attempted to concentrate on the benefits and drawbacks of the model. However, it's possible that the perspective of the customers, who stand to benefit most, was not addressed in that way. The goal of the current study is to focus on the effectiveness of bancassurance from the perspective of consumers.